Study and Characterization ZnO Nanoparticles Prepared by Switched Laser Nd:YAG - Hussein, Jasim Mohamad; Khalel Jasim, Saif; Abdullah, Tariq Faraj; Jasim, Awatif Saber (Indonesian Journal of Material Research, 2024)
In this research, zinc nanoparticles were prepared using pulsed laser ablation in liquids. A pulsed Nd+:YAG laser with wavelength (532 nm) was applied to a pure zinc target immersed in deionized water, and the structural and optical properties of the prepared zinc nanoparticles were studied. The behavior of the UV absorption spectra of zinc nanoparticles was studied as a function of pulse number and ablation energy. The UV-vis absorption spectra showed absorption peaks in the ultraviolet region and in the visible region, the latter being responsible for the formation of zinc nanoparticles, and an increase in the intensity of the absorption peaks with increasing number of laser pulses was observed. Scanning electron microscopy results measured after examining drops of zinc nanoparticle solution showed that the nanoparticles were predominantly spherical in shape with nanoparticle sizes ranging from (42.49, 42.42, and 39.31 nm) respectively, and decreasing in size with increasing ablation pulses, with the best results at higher ablation pulses, the formation of zinc nanoparticles was confirmed by infrared spectroscopy, which confirmed the formation of nanoparticles.